2020
DOI: 10.1186/s13287-020-01602-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transplantation of human induced pluripotent stem cell-derived cardiomyocytes improves myocardial function and reverses ventricular remodeling in infarcted rat hearts

Abstract: Background: Human-induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) have shed great light on cardiac regenerative medicine and specifically myocardial repair in heart failure patients. However, the treatment efficacy and the survival of iPSC-CMs in vivo after transplantation have yielded inconsistent results. Objectives: The objective of this study was to evaluate the ability of human iPSC-CMs to improve myocardial function in a rat postinfarction heart failure model.Methods: Eight-week-old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 31 publications
(40 reference statements)
2
55
0
1
Order By: Relevance
“…Finally, small, and large animal models of HF are important to assess if iPSC-CMs can be a viable treatment for HF. iPSC-CMs can be transplanted as single cells or sheets [42,43,[46][47][48]50,199,200,215,225,226]. Almost all studies, regardless of the animal model used have shown that iPSC-CMs engraft to the host tissue and improve cardiac function, at least transiently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, small, and large animal models of HF are important to assess if iPSC-CMs can be a viable treatment for HF. iPSC-CMs can be transplanted as single cells or sheets [42,43,[46][47][48]50,199,200,215,225,226]. Almost all studies, regardless of the animal model used have shown that iPSC-CMs engraft to the host tissue and improve cardiac function, at least transiently.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the animal model or the clones selected, it is still being debated whether direct injection or the transplantation of iPSC-CM sheets are more beneficial because they all seem to improve cardiac function, at least transiently [42,43,[46][47][48]50,193,199,200,205,206]. While direct injection can allow the injection of cells directly into the damaged tissue, because the heart is in constant motion, iPSC-CMs embedded in scaffolds should allow for better retention.…”
Section: Transplantation Of Ipsc-cms For Treatment Of Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…A third, and possible, the most challenging cause of cell death, is rejection of these allogeneic PSC derivatives. Currently, only drug-based immunosuppression is used to prevent rejection but despite the persisting uncertainties regarding the optimal drug regimen, it is admitted that these drugs are fraught with sideeffects which may lead to their discontinuation with an attendant loss of the grafted cells (Guan et al, 2020). A variant of this approach could be a "biological" immunomodulation by cotransplantation of MSC which have been shown, at least in a subcutaneous implantation model, to control allogeneic iPSC-CM rejection via regulatory T cells and cell-cell contact with activated lymphocytes (Yoshida et al, 2020), however, because MSC are immune evasive and not immune privileged, they can only extend the survival of the co-transplanted iPSC-derived cardiomyocytes without preventing their ultimate disappearance (Yoshida et al, 2020).…”
Section: Cell Survivalmentioning
confidence: 99%